Humoral Immune Response in Japanese Acute Hepatitis Patients with Hepatitis C Virus Infection - N Yamaguchi; K Tokushige; K Yamauchi; N Hayashi (Canadian Journal of Gastroenterology)
The humoral immune response to acute infection by hepatitis C virus (HCV) is not yet perfectly clear in terms of immunoglobulin (Ig) response, diversity of HCV antigen, and the relation with hepatitis severity and antibody response.  Serum IgM and IgG anti-HCV levels in patients with HCV and either acute hepatitis (AH) or fulminant hepatitis (FH) were investigated; the diversity of HCV antigen was investigated by RIBA test III.  Of 22 AH patients, 12 (54.5%) were positive for IgM anti-HCV, mainly reacting to HCV core protein. The mean interval until the appearance of IgM anti-HCV after onset was 24.1±26.2 days. IgG anti-HCV mainly reacted to both core and NS-3 antigen, appearing 42.6±42.1 days after onset.  From a serial study of 15 AH patients, it was considered that in seven AH patients (46.7%), the IgM response would precede the IgG response. In another two AH patients, IgM anti-HCV was not detected during the acute disease phase. Of 48 chronic hepatitis patients with HCV-RNA, 40 patients were positive for IgM anti-HCV.  Therefore, IgM anti-HCV was useful for diagnosis in some of the AH patients, but it was difficult to use for distinguishing between acute and chronic infection. All four FH patients with HCV-RNA were positive for both IgM and IgG antibody to HCV at onset. Their antibody titres were higher than those of AH patients. These results suggested that, as in FH due to HBV, FH due to HCV could induce strong and rapid humoral immunity.